Curriculum Studies in the posthuman condition/posthuman curriculum (studies) - Le Grange, L.; Du Preez, P. (South African Journal of Higher Education, 2023)
In this article we discuss the difference between curriculum studies (as a field of inquiry) in the posthuman condition and posthuman curriculum (studies). The posthuman condition is characterised by both posthumanism and post-anthropocentrism and relates respectively, to how we now define human given humans’ entanglement with new technologies, and the ethical response-ability of humans in intra-action with the more-than-human-world in a context of impending ecological disaster. In this article we shall argue that although Enlightenment humanism has been challenged philosophically/conceptually both in discourses on anti-humanism and posthumanism, humanist approaches to curriculum studies remain with us in the posthuman condition – the ghosts of Dewey, Tyler, Freire, etc., imbue much of curriculum work. However, the posthuman condition also produces posthuman thought that makes it possible to reimagine curriculum studies, that we shall call posthuman curriculum (studies). We shall review different approaches to curriculum studies in the posthuman condition, and then turn our attention to posthuman curriculum (studies). We argue that curriculum (as a vital concept) in posthumanist terms is intelligible and manifests through intra-actions, processes of becoming and experimenting. Set against sedentary states of being that mark curriculum studies in the posthuman condition; becoming, intra-acting and experimenting in posthuman curriculum (studies) are acts, doings in and of this world. The acts and doings in posthuman curriculum (studies) that are mostly written about include: improvisation, theorisation and diffraction. To these we add and specifically discuss quantum tunnelling, tracing, and desiring. Other forms of curriculum experimentation worthy of consideration in posthuman curriculum (studies) but not discussed in the article are queering, imagining, and writing. Towards the end we make the point that although some connections with the past (such as those that haunt curriculum discourses) can be threatening to life, connections of the thick now hold potential and radical openness for newness.